Host genetic loci LZTFL1 and CCL2 associated with SARS-CoV-2 infection and severity of COVID-19 - Rüter, Jule; Pallerla, Srinivas Reddy; Meyer, Christian G.; Casadei, Nicolas; Sonnabend, Michael; Peter, Silke; Nurjadi, Dennis; Linh, Le Thi Kieu; Fendel, Rolf; Göpel, Siri; Riess, Olaf; Kremsner, Peter G.; et al. (International journal of infectious diseases, 2022)
Host genetic factors contribute to the variable severity of COVID-19. We examined genetic variants from genome-wide association studies and candidate gene association studies in a cohort of patients with COVID-19 and investigated the role of early SARS-CoV-2 strains in COVID-19 severity.
Version des Artikels vom 5 July 2022
Gesehen am 20.12.2022